2018
DOI: 10.1016/j.ijmecsci.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of forged Ti-6Al-4V Titanium alloy with microstructural considerations during quenching process

Abstract: The present investigation proposes an experimental device able to assess the thermomechanical behavior of Ti-6Al-4V Titanium alloy throughout the die-forging operation. Constitutive equations are developed to assess the influence of the process (die-forging temperature, cooling rate) and the microstructure parameters on the mechanical response of the alloy. For this purpose, a non-unified behavior model formulation is implemented, which defines two main mechanisms related to α and β phases and allows the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…e heat treatment occurred at above 900°C which resulted in the formation of lamellar beta phase and alpha structures which in turn contributed to the enhancement of mechanical properties. A similar observation was also reported by number of researchers [26][27][28][29][30][31][32].…”
Section: Introductionsupporting
confidence: 88%
“…e heat treatment occurred at above 900°C which resulted in the formation of lamellar beta phase and alpha structures which in turn contributed to the enhancement of mechanical properties. A similar observation was also reported by number of researchers [26][27][28][29][30][31][32].…”
Section: Introductionsupporting
confidence: 88%
“…In recent works [30] , it was shown that at holding up to 10 min in the a + b region with large strains (> 0.4) does not lead to significant softening, and repeated loading does not lead to restrengthening above the level before the interruption. In the region of small deformations in tension, no significant changes in the flow stress after interruption [31,32] are also observed , despite the fact that the stress relaxation significantly increased with increasing temperature.…”
Section: Materials Behaviormentioning
confidence: 92%
“…Titanium alloy Ti-6Al-4V is widely used in various applications such as automotive, biomedical, aerospace, sports marine etc. [28]. Therefore, its powder and bulk material were selected for the experimental verification.…”
Section: Experimental Validationmentioning
confidence: 99%